Późnostarożytne apele o rozpoznanie godności ludzkiej: Bazyli z Cezarei Kapadockiej, Ambroży z Mediolanu, Leon Wielki, Anonim z Werony - Guerrero van der Meijden, Jadwiga (Vox Patrum, 2022)
The article analyses late ancient Christian appeals to recognize human dignity, specifically those formulated by Basil of Caesarea, Ambrose of Milan, Leon the Great and an anonymous Master of Verona. The analyses is divided into parts pertaining to each listed author and finalized with sections investigating firstly, the interrelations between the presented texts as well as a hypothesis of Leo’s reliance on Basil’s and Ambrose’s texts, and secondly, the influences of the appeals on the subsequent centuries. The study points to biblical, ancient Greek and Roman inspirations of various calls. I argue that Leo’s formulation is indirectly inspired by the Delphic gnothi seauton formula that was specified by the Christian thinkers to human axiological status and filled in with biblical expressions.